The Basal Forebrain Modulates Neuronal Response in an Active Olfactory Discrimination Task - Nunez-Parra, Alexia; Cea-Del Rio, Christian A.; Huntsman, Molly M.; Restrepo, Diego (Frontiers in Cellular Neuroscience, 2020)
Successful completion of sensory decision-making requires focusing on relevant stimuli, adequate signal to noise ratio for stimulus discrimination and stimulus valence evaluation. Different brain regions are postulated to play a role in these computations, however, evidence suggests that sensory and decision-making circuits are required to interact through a common neuronal pathway to elicit a context-adequate behavioral response. Recently, the basal forebrain (BF) region has emerged as a good candidate, since its heterogeneous projecting neurons innervate most of the cortical mantle and sensory processing circuits modulating different aspects of the sensory decision-making process. Moreover, evidence indicates that the BF plays an important role in attention and in fast modulation of neuronal activity that enhance visual and olfactory sensory perception. Here, we study in awake mice the involvement of BF in initiation and completion of trials in a reward-driven olfactory detection task. Using tetrode recordings we find that BF neurons (including cholinergics) are recruited during sensory discrimination, reward and interestingly slightly before trial initiation in successful discrimination trials. The pre-cue neuronal activity was correlated with animal performance, indicating that this circuit could play an important role in adaptive context-dependent behavioral responses.